2009
DOI: 10.1136/hrt.2008.156646
|View full text |Cite
|
Sign up to set email alerts
|

Elevated glycated haemoglobin is a strong predictor of mortality in patients with left ventricular systolic dysfunction who are not receiving treatment for diabetes mellitus

Abstract: The abrupt increase in mortality with HbA1c may make it a useful risk stratification tool in non-diabetic patients with LVEF

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 40 publications
2
41
0
3
Order By: Relevance
“…This might be partly attributed to differences both in the study design and in the clinical characteristics of patients enrolled in the GISSI‐HF trial (which was essentially a pragmatic, all‐comer–oriented clinical trial) and in the PARADIGM‐HF trial (which adopted very strict enrollment criteria, including the presence of LVEF <35% and the study drug tolerability in a long run‐in observational period). However, our findings are also consistent with those reported by Goode et al,14 who did not observe any significant increase in the risk of all‐cause death among nondiabetic CHF patients with a HbA1c level less than 6.5%.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This might be partly attributed to differences both in the study design and in the clinical characteristics of patients enrolled in the GISSI‐HF trial (which was essentially a pragmatic, all‐comer–oriented clinical trial) and in the PARADIGM‐HF trial (which adopted very strict enrollment criteria, including the presence of LVEF <35% and the study drug tolerability in a long run‐in observational period). However, our findings are also consistent with those reported by Goode et al,14 who did not observe any significant increase in the risk of all‐cause death among nondiabetic CHF patients with a HbA1c level less than 6.5%.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, few studies have investigated the prevalence of pre‐DM in patients with CHF and even fewer its clinical consequences (and with conflicting findings) 9, 14, 20, 24…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of glucose intolerance in patients with HF was reported in several trials range from 23% to 43% [24][25][26][27] . A recent study conducted in Kameda Medical Center, Chiba, Japan showed that out of 136 subjects 46 (33.82%) had prediabetes, among them 9 (9.6%) had IFG, 37 (39.4%) had IGT 28 .…”
Section: Discussionmentioning
confidence: 99%
“…From the publication of the UKPDS study onwards almost all studies targeting HbA1c levels <7.5% failed to show a cardiovascular benefit and often demonstrated an increased risk of cardiovascular mortality and morbidity, most often related to heart failure. [1,[14][15][16][17][18] In patients with heart failure and coexisting diabetes mellitus maintenance of adequate glycaemic control is a critical issue not only because of the relationship between glucose levels, heart function and outcomes but also because the choice of drugs available to safely manage glucose management in patients with heart failure is limited. [8,9] A meta-analysis of 13 high quality studies on 34,533 patients showed that intensive glucose lowering is not associated with any significant reduction in cardiovascular risk but conversely results in a 47% increase in HF risk (P<0.001).…”
Section: Introductionmentioning
confidence: 99%